Effect of static stretching of quadriceps and hamstring muscles on knee joint position sense. Issue 1 (23rd December 2004) - Larsen, R; Lund, H; Christensen, R; Røgind, H; Danneskiold-Samsøe, B; Bliddal, H
Abstract : Objectives: To evaluate if a stretch regimen consisting of three 30 second stretches would alter joint position sense (JPS). Methods: A blinded, randomised, cross over design with a washout time of 24 hours was used with 20 healthy volunteers. JPS was estimated from the ability to reproduce the same position in one knee (target versus estimated angle) expressed as the difference between target and estimated angle (constant error, CE). Measurements were repeated three times in a sitting and a prone position on the dominant leg measured before and immediately after the static stretch. The static stretch consisted of a 30 second stretch followed by a 30 second pause, repeated three times. Results: At baseline, the mean (SD) CE was −2.71 (3.57)° in the sitting position. No difference (p = 0.99) in CE between stretching and control was observed (0.00; 95% confidence interval −0.98 to 0.99). At baseline, the CE was −3.28 (4.81)° in the prone position. No difference (p = 0.89) in CE between stretching and control was observed (0.12; 95% confidence interval −1.52 to 1.76). Conclusion: A static stretch regimen had no effect on JPS in healthy volunteers.